Broadband, High-Linearity Switches for Millimeter-Wave Mixers Using Scaled SOI CMOS - Cameron Hill; James F. Buckwalter (IEEE Open Journal of the Solid-State Circuits Society)
This work demonstrates new circuit techniques in distributed-stacked-complimentary (DiSCo) switches that enable picosecond switching speed in RF CMOS SOI switches. By using seriesstacked devices with optimized gate impedance and voltage swing, both high linearity and fast switching are possible. A theoretical analysis and design framework has been developed and verified through simulation and measurement through two broadband, high-linearity passive mixer designs, one optimized for linearity and the other for bandwidth, using a 45-nm SOI CMOS process. The mixers achieve $P_{1dB}{s}$ of 16-22 dBm with $IIP3s$ of 25-34 dBm across a bandwidth from 1 GHz up to 30 GHz. This performance exceeds prior SOI RF and microwave mixer performance by more than an order of magnitude and is comparable to III-V device technologies. The mixers include integrated local oscillator (LO) driving amplifiers for high efficiency operation and low total power consumption. DC power consumption ranges from 250 mW to 1 W for the LO driver. The integrated LO drivers demonstrate a pathway to on-chip LO generation with simplified matching to maximize LO power delivered to the input of the switch.